Participação de citocinas relacionadas às respostas Th17/Treg na inflamação periapical inflamatória crônica - Andre Oliveira Naufel de Toledo (2017)
Inflammatory periapical disease is a sequel of the infection and pulp necrosis. It represents the host defense response to aggression from the root canal. Chronic periapical lesions are developed in response to the maintenance of inflammation and bone resorption. Regulatory T cells (Tregs) and Th17 cells play a key role in regulating the immune response with opposite functions. Forkhead box P3 (FoxP3) is the master transcription factor for Treg cells, but differentiation and maturation of naive T cells in Treg or Th17 also depend on specific cytokines such as transforming growth factor (TGF), interleukin 10 (IL -10), interleukin-17 (IL-17), interleukin-6 (IL-6) and interleukin-21 (IL-21). Other cytokinesparticipate in the modulation of the Treg and Th17 activity, as the chemokines CCL4 and CCL20 with function of recruitment of these cells to act in the inflammatory process. The role of Treg and Th17 has been better studied in autoimmune diseases, but sparsely evaluated in the pathogenesis of chronic periapical inflammatory lesions. Eighty-six human samples were used to perform histologic analysis and the cytokine dosage by enzyme-linked immunosorbent assay (ELISA) (TGF-, IL-10, IL-17, CCL4, CCL20) in the periapical tissue of three groups: control group, group of teeth with pulp necrosis and periapicallesion and group of teeth with necrosis without periapical lesion. We observed high expression of CCL4 and TGF- in the group with periapical lesion in comparison with the groups without lesion and demonstrated increased expression of CCL20 in the group with periapical lesion when compared to control. Our findings imply that these two characteristics, pro-inflammatory and immunosuppressive, are present in the chronic periapical lesion, occurring simultaneously and with co-stimulation characteristics, as a result of the intense actionof the host's immune response against the inflammatory process coming from intracanal bacteria and their by-products.